A Person-centered Approach to Violence Exposure in Postwar Colombian Youth: Demographic Covariates and Positive Youth Development Outcomes - Fraser, Ashley M. (Journal of interpersonal violence, 2022)
While the negative impact of extensive exposure to community violence and armed conflict is known, less emphasis has been focused on outcomes supportive of resilience. It is critical to begin exploring these constructs to both promote healing from decades-long conflict and to inform targeted interventions that focus on positive youth development in contexts of adversity. This study thus utilized a person-centered approach to estimate violence exposure profiles among 3,443 Colombian youth to explore what demographic covariates and positive youth development outcomes, such as school engagement, hope, goals, social competence, future expectations, and barriers to education were associated with each violence exposure profile. Four profiles emerged: a low exposure profile, a high community violence profile, a some combined exposure profile, and a high combined exposure profile, each with various levels of community violence witnessing and victimization as well as armed conflict exposure. Demographic covariance results showed older, urban, male youth were more likely to be in the high violence exposure profiles compared to the low exposure group. Youth in the high combined exposure profile were more likely to have lower hope, educational expectations, and social competence compared to the low exposure group. Findings highlight that a person-centered approach provides a more multidimensional view of adolescent violence exposure. Demographic differences suggested the importance of tailoring violence prevention initiatives to the local context. Finally, results concerning positive youth development outcomes suggest that resiliency-oriented constructs, which can be instrumental toward youth?s postwar healing and growth, should be emphasized among populations who experience high levels of co-occurring exposure.